Janus silver/ternary silver halide nanostructures as plasmonic photocatalysts boost the conversion of CO2 to acetaldehyde. Issue 47 (25th November 2021) - Jia, Henglei; Dou, Yanrong; Yang, Yuanyuan; Li, Fan; Zhang, Chun-yang
Abstract : Janus Ag/AgClBr nanostructures were constructed using a facile method for the boosting conversion of CO2 to 10-electron reduction product CH3 CHO. Abstract : Photocatalytic conversion of carbon dioxide (CO2 ) to liquid product acetaldehyde (CH3 CHO) remains a great challenge due to the involvement of a complex 10-electron reduction process and a sluggish C–C coupling reaction. Herein, we report the synthesis of Janus silver/ternary silver halide (Ag/AgClBr) nanostructures through precisely manipulating the growth kinetics and its function as a plasmonic photocatalyst to boost the conversion of CO2 to CH3 CHO. The obtained Janus nanostructures featuring both spatially separated architecture and broad light-harvesting capability facilitate the photocatalytic reduction of CO2 under solar illumination. The photocatalytic CO2 reduction with the characteristics of high activity and good selectivity can generate a 10-electron reduction product CH3 CHO with a generation rate of 209.3 ± 9.5 μmol h −1 g −1 and a selectivity of 96.9%, which are rarely achieved in previously reported photocatalytic CO2 reduction systems. The excellent photocatalytic performance can be ascribed to the plasmonic effect of Ag nanocrystals and the favorable active sites on the catalyst surface. This research demonstrates for the first time the utilization of the Janus Ag/AgClBr nanostructures to generate the value-added C2 liquid product through photocatalytic CO2 reduction, paving the way for the design and construction of novel plasmonic photocatalysts.